2020
DOI: 10.1177/0300891620910805
|View full text |Cite
|
Sign up to set email alerts
|

High expression of RAD21 predicts poor survival in patients with operated non-small-cell lung cancer

Abstract: Purpose: To investigate the expression profile and prognostic value of RAD21 in patients with non-small cell lung cancer (NSCLC). Methods: A tissue microarray (TMA) containing 60 paired NSCLC tissues and peritumor tissues was purchased and another TMA containing 140 NSCLC tissues was constructed. Then, immunohistochemical staining was performed and scored. Finally, the expression profile and prognostic value of RAD21 were evaluated. Results: RAD21 was predominantly detected in the nucleus of tumor and peritumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Besides, It has also been proven that the higher RAD21 expression in tumor tissues is associated with shorter DSS of patients with colorectal cancer. Also, the higher expression of RAD21 in patients promotes the resistance of chemoradiotherapy and chemotherapy (36). All in all, our results are consistent with the previous studies, and the function of RAD21 in colon cancer further indicates that GSTM2 may be involved in tumor formation as a suppressor.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Besides, It has also been proven that the higher RAD21 expression in tumor tissues is associated with shorter DSS of patients with colorectal cancer. Also, the higher expression of RAD21 in patients promotes the resistance of chemoradiotherapy and chemotherapy (36). All in all, our results are consistent with the previous studies, and the function of RAD21 in colon cancer further indicates that GSTM2 may be involved in tumor formation as a suppressor.…”
Section: Discussionsupporting
confidence: 92%
“…RAD21 encodes a subunit of cohesin, and mainly involved in modifying the adhesion and separation of sister chromatids, thus regulating gene transcription and DNA damage repairing. Numerous studies have revealed that RAD21 is over expressed in a variety of tumors, such as colorectal cancer, non small cell lung cancer, and breast cancer (35)(36)(37). Besides, It has also been proven that the higher RAD21 expression in tumor tissues is associated with shorter DSS of patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the prognostic impact of RAD21 alterations. Previously, it was reported that RAD21 overexpression is a marker for poor prognosis in breast [ 48 50 ], bladder [ 51 ], KRAS mutant colorectal carcinomas [ 52 ], and NSCLC [ 53 ]. Our results are in line with this finding, where patients with RAD21 altered breast invasive ductal carcinoma had significantly worse median overall survival compared to their WT counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…RAD21 expression in colorectal cancer cells was modulated by Wnt/β-catenin activation and was associated with shorter disease-specific survival in patients with KRAS mutant tumors ( 11 , 25 ). Furthermore, high RAD21 expression conferred poor survival in patients with non-small cell lung cancer, especially in stages II–III ( 26 ). However, the correlation between RAD21 and ovarian cancer prognosis has not been clarified.…”
Section: Discussionmentioning
confidence: 99%